A Consensus Approach for Targeted Muscle Reinnervation in Amputees. Issue 4 (5th April 2023) - Eberlin, Kyle R.; Brown, David A.; Gaston, R. Glenn; Kleiber, Grant M.; Ko, Jason H.; Kovach, Stephen J.; Loeffler, Bryan J.; MacKay, Brendan J.; Potter, Benjamin K.; Roubaud, Margaret S.; Souza, Jason M.; Valerio, Ian L.; et al.
Abstract : Amputations have been performed with few modifications since the dawn of surgery. Blood vessels are ligated, bones are shortened, and nerves are cut. In a percentage of people, this can result in severe neuropathic, residual limb, and phantom limb pain. Targeted muscle reinnervation is a surgical procedure initially conceived to optimize function for myoelectric prostheses in amputees. Recently, it has been adopted more widely by surgeons for the prevention and treatment of neuropathic pain. Perhaps as a function of its relatively recent development, many authors perform this operation differently, and there has been no overall agreement regarding the principles, indications, technical specifics, and postoperative management guidelines. This article is written as a consensus statement by surgeons focused on the treatment of neuropathic pain and those with extensive experience performing targeted muscle reinnervation. It is designed to serve as a roadmap and template for extremity surgeons to consider when performing targeted muscle reinnervation.